PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN KEPEMIMPINAN TERHADAP KINERJA PERANGKAT DESA PADA KANTOR DESA KESAMBIRAMPAK DAN DESA KAPONGAN KABUPATEN SITUBONDO MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Ramdani, Dicky; Fandiyanto, Randika; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Organizations have various kinds of resources as input to transform an environment into a productive one with the division of labor, human resources are also the most important element. The aim of this research is to analyze and test the influence of organizational culture, work environment and leadership on the performance of village officials through work motivation as an intervening variable. The population used in this research was Village Officials at the Kesambirampak Village Office and Kapongan Village, Situbondo Regency, a total of 33 people were selected. This sampling technique is saturated sampling. Data analysis and hypothesis testing in research uses Structural Equation Models - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Organizational culture has a significant positive effect on work motivation. The work environment has a significant positive effect on work motivation. Leadership has a significant positive effect on work motivation. Organizational culture has a negative but not significant effect on performance. The work environment has a positive but not significant effect on. Leadership has a negative but not significant effect on performance. Work motivation has a significant positive effect on performance. Then the results of the indirect influence hypothesis test show that the organizational culture variable on performance through work motivation has a significant positive effect. The work environment on performance through work motivation has a positive but not significant effect. Leadership on Performance through work motivation has a significant positive effect